KONSEP DAKWAH PENDEKATAN TEMATIK PERSPEKTIF ALQURAN - Rangkuti, Nurazizah (Yayasan Baitul Hikmah al-Zain, 2024)
Islam is the last religion revealed by Allah to the Prophet Muhammad SAW. Even though there were no apostles after him, the task of preaching was still continued by the ulama as successors of the teachings. Every Muslim has the obligation to preach according to his abilities and knowledge, regardless of social status. The Qur'an emphasizes the importance of da'wah through wise invitations, warnings of goodness, and prevention of evil. With terms such as tabligh and nashihat, da'wah functions to guide individuals and society towards the correct understanding and practice of Islam. The research method used in this paper is library research. This research collects, reads and analyzes various references related to the concept of da'wah from the perspective of the Qur'an, including books, articles and journals. With this approach, it is hoped that it can provide a deep understanding of da'wah and its role in Islam. Da'wah must be carried out with careful planning and an approach that is appropriate to the context of society to reach all levels. The preacher's morals are very important; they must reflect Islamic values ​​in their daily behavior and prepare themselves with knowledge and strong faith. Thus, da'wah is not just an activity, but is a fundamental responsibility for every Muslim to spread goodness and protect society from damage.